2007
DOI: 10.1152/ajpendo.00516.2007
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical dysregulation as a major player in insulin resistance and onset of obesity

Abstract: The aim of this review is to explore the dysregulation of adrenocortical secretions as a major contributor in the development of obesity and insulin resistance. Disturbance of adipose tissue physiology is one of the primary events in the development of pathologies associated with the metabolic syndrome, such as obesity and type 2 diabetes. Several studies indicate that alterations in metabolism of glucocorticoids (GC) and androgens, as well as aldosterone in excess, are involved in the emergence of metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 217 publications
(239 reference statements)
2
53
0
1
Order By: Relevance
“…Its role is not yet clearly defined, since it does not modify proliferation or protein synthesis in isolated cells (Otis et al 2005). However, several recent data have suggested that AT 2 R may ensure a protective role not only in the cardiovascular and renal systems (Carey & Padia 2008, Siragy 2009), but also in metabolic homeostasis, brain disorders and even in cancer (for reviews, see Henriksen (2007), Roberge et al (2007), Horiuchi et al (2010) and Steckelings et al (2010)). The change in protein levels of AT 1 R and AT 2 R in IUGR males in the present study led to a decrease in AT 1 R to AT 2 R ratio, which may have contributed to the observed reduction in aldosterone synthesis.…”
Section: Adrenal Changes Induced By Nacl Supplementationmentioning
confidence: 99%
“…Its role is not yet clearly defined, since it does not modify proliferation or protein synthesis in isolated cells (Otis et al 2005). However, several recent data have suggested that AT 2 R may ensure a protective role not only in the cardiovascular and renal systems (Carey & Padia 2008, Siragy 2009), but also in metabolic homeostasis, brain disorders and even in cancer (for reviews, see Henriksen (2007), Roberge et al (2007), Horiuchi et al (2010) and Steckelings et al (2010)). The change in protein levels of AT 1 R and AT 2 R in IUGR males in the present study led to a decrease in AT 1 R to AT 2 R ratio, which may have contributed to the observed reduction in aldosterone synthesis.…”
Section: Adrenal Changes Induced By Nacl Supplementationmentioning
confidence: 99%
“…Human adipocytes produce mineralocorticoid-releasing factors that stimulate aldosterone secretion, which in turn promotes adipogenesis (11,13,14). Furthermore, epidemiological studies demonstrate that high plasma aldosterone concentrations (PAC) are associated with impaired insulin metabolic signaling, impaired pancreatic b-cell function, and insulin resistance (15,16). In crosssectional analyses, associations of aldosterone with MetS were demonstrated (9,17).…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids play a critical role in inducing the adipocyte cell fate and differentiation both in vivo and ex vivo (1)(2)(3). This regulatory process may be relevant to normal physiology and to disease states, as patients exposed chronically to excess glucocorticoids develop increased adiposity (4).…”
mentioning
confidence: 99%